2008
DOI: 10.1002/cphc.200800109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Solvent on the Conformation of Isolated MEH‐PPV Chains Intercalated Into SnS2

Abstract: Photophysical processes in conjugated polymers are influenced by two competing effects: the extent of excited state delocalization along a chain, and the electronic interaction between chains. Experimentally, it is often difficult to separate the two because both are controlled by chain conformation. Here we demonstrate that it is possible to modify intra-chain delocalization without inducing inter-chain interactions by intercalating polymer monolayers between the sheets of an inorganic layered matrix. The red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The film patterns of SnS 2 restacked with the different polymers all show an intense reflection at 5.8 (2 q = 15.48), corresponding to the caxis interlayer spacing of SnS 2 single crystals, [37] and an additional peak at 11 (2 q = 8.58), corresponding to the (001) reflection of polymer-incorporated SnS 2 . The expansion of the interlayer spacing by about 5 to accommodate the polymer guest species is in good agreement with the c-axis expansion observed for the intercalation of polyaniline, [38] polyfluorene, [15] or poly[2-methoxy-5-(2'-ethylhexyloxy)-1,4-phenylene vinylene] [36] monolayers into layered hosts. The ratio of the intensity of the peak at 8.58 to that at 15.48 in all patterns shown in Figure 2 is about 0.25 and implies that about a quarter of the layers in each of the samples are intercalated with polymer.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The film patterns of SnS 2 restacked with the different polymers all show an intense reflection at 5.8 (2 q = 15.48), corresponding to the caxis interlayer spacing of SnS 2 single crystals, [37] and an additional peak at 11 (2 q = 8.58), corresponding to the (001) reflection of polymer-incorporated SnS 2 . The expansion of the interlayer spacing by about 5 to accommodate the polymer guest species is in good agreement with the c-axis expansion observed for the intercalation of polyaniline, [38] polyfluorene, [15] or poly[2-methoxy-5-(2'-ethylhexyloxy)-1,4-phenylene vinylene] [36] monolayers into layered hosts. The ratio of the intensity of the peak at 8.58 to that at 15.48 in all patterns shown in Figure 2 is about 0.25 and implies that about a quarter of the layers in each of the samples are intercalated with polymer.…”
Section: Resultssupporting
confidence: 76%
“…[35] To study 2D energy transfer in conjugated polymers, PF and PF with 1, 2, or 5 mol % fluorenone defects were separately incorporated into layered SnS 2 by the procedure recently reported for incorporation of conjugated polymers into inorganic layered compounds. [15,36] In this process, Li atoms are intercalated into the interlayer galleries of SnS 2 , followed by exfoliation of Li x SnS 2 to form a suspension of SnS 2 single layers. Restacking the SnS 2 layers in the presence of the conjugated polymers effectively encapsulates the polymer chains between two adjacent SnS 2 layers.…”
Section: Resultsmentioning
confidence: 99%
“…Ensemble spectroscopic measurements have shown that CP chains in the solvents used here are isolated, well solvated, and contain few, if any, intra-chain contacts. [18][19][20] In a spin-coated MEH-PPV/PMMA film, SMS data show a heterogeneous distribution of collapsed CP chain conformations, including subpopulations of relatively disordered conformations that are kinetically trapped in a high energy state and ordered conformations with a low energy state. During SVA, the film resides in a heterogeneous mixture of solid and liquidlike phase in which the CP chains undergo folding/unfolding events between a collapsed and an extended conformation.…”
mentioning
confidence: 99%
“…On the one hand, conjugated polymers have enormous technological potential as low-cost, easily processed materials open to a diverse set of applications, including biomedical sensors, inexpensive solar cells, light-emitting diodes, and printable electronics. On the other hand, solution-processing methods are highly complex at the molecular level, which prevents the development of rational design approaches to improve these methods. During processing, conjugated polymers are first dissolved in a suitable solvent, in which they can form a random coil structure with few, if any, inter- and intrachain contacts. Second, the material is processed by different methods, for example, doctor-blading, , drop-casting, or spin-casting, , and the conjugated polymers form a neat solid film during the evaporation of the solvent. The film morphology is mainly determined by the second step and depends on a variety of parameters, such as solvent quality, evaporation rate, and substrate surface .…”
mentioning
confidence: 99%